2019
DOI: 10.1088/1757-899x/586/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Study regarding the stiffness influence of slab to beams for a plan structural reinforced concrete frame system in seismic zones

Abstract: For monolithic reinforced concrete structures, it is known that beams and slabs form a common body, so that the stiffness of the dissipative elements (beams) increases significantly. Also, it is known the fact that the beams are the principal structural dissipative elements. In these circumstances, it will try through numerical simulations (nonlinear calculation) a theoretical reproduction of a recently executed structure, so as to take into consideration the effect of excess rigidity brought to the horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Another particular effect produced by the RC slab is the development of the "common rigid block (RC beams-slab-node)" [15][16][17], [34] which can lead to the appearance of the "soft story mechanism" [5], after severe earthquake loading of the structure.…”
Section: Global Analytical Results Regarding Pushover Analysesmentioning
confidence: 99%
“…Another particular effect produced by the RC slab is the development of the "common rigid block (RC beams-slab-node)" [15][16][17], [34] which can lead to the appearance of the "soft story mechanism" [5], after severe earthquake loading of the structure.…”
Section: Global Analytical Results Regarding Pushover Analysesmentioning
confidence: 99%
“…In essence, the present paper aims to validate the mechanical weakening (of resistance and lateral stiffness) method of dissipative structural elements-reinforced concrete beamsin the design stage, highlighting the emergence of the common rigid block "beams-slabframe nodes" [51].…”
Section: General Aspectsmentioning
confidence: 99%
“…Thus, the linear elastic structural elements (RC columns, RC beam-column joints) maintain their integrity through oversizing and the ductile structural elements dissipate the seismic energy by means of plastic hinges. This aspect was emphasized in a recent research work [2] on assessing the seismic behaviour of a GF+3F RC moment resisting frame. The 2D model considered a single value for the behaviour factor, in accordance with the actual seismic regulations [3,26].…”
Section: Theoretical and Analytical Aspects Regarding The Improvement...mentioning
confidence: 99%
“…For the case presented in a recent study [2] and considering the graph shown in Fig. 3, the bending constant stiffness difference between RC columns and RC beams is given in Eq.…”
Section: Theoretical and Analytical Aspects Regarding The Improvement...mentioning
confidence: 99%
See 1 more Smart Citation